Analisis Yuridis Putusan Pengadilan Agama Kediri Nomor 0457/Pdt.G /2016/PA. Kdr Tentang Perkara Ekonomi Syari’ah - Evi Nurvita Sari; Imam Annas Mushlihin; Abdullah Taufik (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2020)
Completion of the Syari'ah Economic case is the authority of the Religious Court as stated in Article 49 of Act Number 3 of 2006 concerning Judicial Power. This syari'ah economic case Number 0457 / Pdt.G / 2016 / PA.Kdr was submitted by a Syari'ah Bank customer who felt losing because collateral was auctioned by the Syari'ah Bank through the State Wealth and Auction Service Office (KPKNL). If the auction process is carried out, the customer as the Plaintiff will suffer a large loss. On this basis the plaintiff through his legal counsel filed a lawsuit to the Kediri Religious Court. This study used a qualitative approach with normative juridical analysis of the legal documents of the decision of the Kediri Religious Court. This thesis discusses how the basis of legal considerations, the claim of the plaintiffs was declared not accepted (niet ovankelijke verklaard) and the legal implications of the Decision of the Kediri Religious Court Number 0457 / Pdt.G / 2016 / PA.Kdr. The conclusion of the above writing is as follows: First, the basic legal considerations of the decision of the Kediri Religious Court Number 0457 / Pdt.G / 2016 / PA.Kdr are the Jurisprudence of the Supreme Court of the Republic of Indonesia Number 1149 / K / Sip / 1975 dated 17 April 1975 jo. Decision of the Supreme Court of the Republic of Indonesia Number 565 / K / Sip / 1973 dated August 21, 1973, jo. verdict of the Supreme Court of the Republic of Indonesia Number 1149 / K / Sip / 1979 dated April 7, 1979 which states that the object of the claim is unclear, the claim cannot be accepted (niet ovankelijke verklaard). Second, the legal implications of the verdict are final and binding, judicially the ruling causes harm to the plaintiff, besides the principal case is not decided, the plaintiff is also burdened with court fees. Keywords: Juridical Analysis, Decision of the Religious Court, Syari'ah Economy.